In vitro inhibition attempts and bio-elicitation of Solanum lycopersicum L. by chitin and chitosan against Ralstonia solanacearum, the causal agent of bacterial wilt - Amine Rkhaila; Mouhatti Saga; Sofia Ghizlan Grohs; Khadija Ounine (Agronomía Colombiana, 2021)
Ralstonia solanacearum is one of the most destructive pathogens of vegetables causing very important economic losses. In 2019, 20 strains of R. solanacearum were collected from potato tubers in Morocco. After their identification, the inhibitory effect of colloidal solutions of chitin and/or chitosan was evaluated in vitro on a solid medium (Mueller Hinton) supplemented with these biopolymers. The concentrations (25, 50, or 100 mg L-1) contributed to significant inhibition of the growth of the isolated strains that led to an inhibition of 45.04% with the combination of chitin-chitosan (100 mg L-1), 58.92% with the addition of 100 mg L-1 of chitin, and 68.74% in the presence of chitosan at 25 mg L-1. Likewise, in experiments with Solanum lycopersicum L. seedlings, chitin derivatives significantly promoted stem and root growth. Stem length increased by 54.95% when chitin was added at 25 mg L-1, while soil amendment with 100 mg L-1 of chitosan increased root length by 82.55% compared to the control. The severity of bacterial wilt due to R. solanacearum was reduced by 117.02% when we added 100 mg L-1 of chitosan to the soil. However, the severity of this disease decreased by 142.86% when the soil was amended with chitin at 50 mg L-1. These findings are consistent with prior research that suggests using this technique to manage bacterial wilt caused by R. solanacearum.